ZAKAT WITHIN THE FRAME OF THE UNITARY STATE REPUBLIC OF INDONESIA: ADAPTABILITY OF SHARIA VALUES AND CULTURES - M Usman (Indonesian Journal of Islamic Literature and Muslim Society, 2021)
This paper aims to elaborate the dynamics of Islamic law assimilation with local culture. With the hope that in the future it will form a basic perspective in shaping the philanthropy of contemporary Islamic law based on the reality of Indonesian society. The basic questions which is going to be answered through this paper are, first, the extent of the adaptability of Islamic law in the midst of multicultural society conditions in Indonesia. Second, what are juridical, normative and sociological arguments in placing zakat as a support for the integrity of the Unitary State Republic of Indonesia. Third, How is the Formulation of the Concept of Zakat within the frame of Unitary State Republic of Indonesia?Â The conclusion from this study shows that, first, the characteristics of Islamic law indicate the ability of adaptability to the culture of the society in which it is accepted. Even in this case Islam has provided important principles regarding rational development in efforts to adapt to its new environment. Second, placing zakat as a support for the integrity of the Unitary State Republic of Indonesia is worth to be formulated. This is a logical consequence of the efforts of the Islamic ummah to always place al-Qur'an and al-Sunnah as limited texts. One of the most fundamental results of Indonesian social culture is the realization of the Unitary State of the Republic of Indonesia. Making the formulation of zakat in the frame of the Unitary State Republic of Indonesia is a clear proof that Islamic law contains universal values that are valid in any time and any place. Third, the methodological formulation of zakat in the frame of Unitary State of the Republic of Indonesia is in a dynamic and accommodating ijtihad towards change. This methodological framework is based on al-Mashlahah, â€˜Urf, Sad Dzaria'ah and dialectics between Gama and the State.